Pengaruh Motivasi Terhadap Kinerja Karyawan Pada PT. United Tractors Tbk. Cab. Medan - Della Aula Dina; Ade Rahma Ayu (CIVITAS: Jurnal Studi Manajemen, 2022)
The purpose of this research is to find out if there is a motivational effect on employee performance in PT. United Tractors Tbk. CAB. Medan. The sample of this study was 30 people all permanent employees. Sampling techniques used census techniques. Data analysis used a simple linear regression test, while data processing used SPSS. The results showed that motivation had a positive and significant effect on performance partially.